Música, educação e democracia - Santos, Marco Antonio Carvalho (2004)
This work discusses musical education departing from a view of music as praxis. It tries to situate this teaching both in the context of the tense and contradictory relations established between education and democracy in Brazil and before the new configurations in the field of culture in the contemporary capitalist societies, marked by what Jameson characterized as a fusion between culture and economy. Adorno s analysis of the transformations in the field of culture, and more specifically, of music has produced an analytical tool considered essential for the understanding of the phenomena here approached. The project entitled Música na Escola (Music at School), developed by Conservatório Brasileiro de Música (Brazilian Conservatory of Music) and Secretaria Municipal de Educação do Rio de Janeiro (Municipal Secretary of Education in Rio de Janeiro) between 1999 and 2002 is looked into as an educational experience which attempted to propose pathways for musical education and, despite the fact it was interrupted, it enables reflections upon some quandaries and limitations of the educational politics in the teaching of music.